Environmental protection as market pathology?: carbon trading and the dialectics of the 'double movement' - Carton, Wim (Environment & Planning D: Society & Space, 2014)
Polanyi's concept of the 'double movement' is frequently interpreted as the opposition between the problematic and unsustainable dynamics of the market and the benign and normatively desirable reaction against this by 'society'. This paper questions this dualistic interpretation of the double movement and undertakes a problematization of the Polanyian idea of social and environmental protection. It does this by revisiting the concept of the double movement in light of the recent proliferation of market-based mechanisms for environmental regulation. Through an exploration of the different interpretations of Polanyi's work, the paper presents a dialectical reading of the double movement that conceptualizes the idea of social protection within a broader capitalist framework. This is then illustrated with the case of emissions trading as a particular form of environmental protection. Carbon trading as a mitigation strategy, it is argued, corresponds to the Polanyian idea of 'social protection' in that its protective potential to reduce emissions is itself constrained by the socioeconomic framework within which it operates. This in turn points to the need for a critique of climate mitigation efforts that goes beyond a focus on current problems with emissions trading schemes.
Geography
Keywords: EU Emissions Trading Scheme; carbon offsetting; climate change; countermovement; emissions trading; environmental protection; pathology; socioeconomics

On the Nature of the Countermovement: A Response to Stuart et al.’s ‘Climate Change and the Polanyian Countermovement: Carbon Markets or Degrowth?’ - Carton, Wim (New Political Economy, 2020)
In a recent article for this journal, Stuart, D., Gunderson, R., and Petersen, B. [(2017). Climate change and the Polanyian counter-movement: carbon markets or degrowth? New political economy, 1–14. doi:10.1080/13563467.2017.1417364] discuss solutions to climate change in terms of Karl Polanyi’s concept of the double movement. They set up their argument as a critique of my own article on the topic to make the point that carbon markets do not constitute a genuine form of such countermovement. I’m sympathetic to the critique of carbon markets that the authors present, as well as their discussion of degrowth, which mirrors a by now extensive literature demonstrating the pitfalls respectively the necessity of these diametrically opposed approaches to the current socioecological crisis. However, in setting up their case the authors provide an overly optimistic reading of Polanyi that I believe misses a crucial part of his argument, a reading that at least partly explains our differences in opinion. This commentary offers a friendly critique of Stuart et al.’s use of Polanyi and clarifies the argument in my previous text that the authors take issue with.
Political Science; Environmental Studies
Keywords: Polanyi; carbon markets; climate change; commodification; countermovement